Theoretical analysis of centrifugal dewatering of superabsorbent hydrogels using Terzaghi–Voigt combined model - Jami, Mohammed Saedi; Iwata, Masashi (Elsevier, 2007)
This paper presents results of experimental work carried out to study the centrifugal dewatering behaviors of superabsorbent hydrogels. Taking the creep deformation of the hydrogels into consideration and assuming that the mechanical properties of gel network can be represented by Terzaghi–Voigt combined model, the basic differential equation expressing the centrifugal dewatering of superabsorbent hydrogels is solved. The progress of centrifugal dewatering is represented by an average consolidation ratio Uc as in mechanical expression. The agreement between calculated and experimental Uc is satisfactory when the creep deformation of the material is considered. Consistent with mechanical expression and electroosmotic dewatering, as the driving force for centrifugal dewatering increases, the modified consolidation coefficient of the hydrogel network Ce also increases. Effectiveness of centrifugal dewatering, expressed as a relative difference between the initial void ratio and final void ratio, increases with the rotational speed. For a given rotational speed, the final void ratio remains constant regardless of the initial weight of the gel. On the other hand, as the rotational speed of the centrifuge gets higher, the final void ratio decreases for all initial weights of the gel investigated in the current study. The magnitude of creep deformation B depends upon the amount of initial weight of the hydrogel. For a given rotational speed of the centrifuge, the magnitude of creep deformation becomes larger as the initial amount of hydrogel is increased. 2007 Elsevier Ltd. All rights reserved.